Endothelial-specific Nox2 overexpression increases vascular superoxide and macrophage recruitment in ApoE⁻/⁻ mice. - Douglas, G; Bendall, J; Crabtree, M; Tatham, A; Carter, E; Hale, AB; Channon, K (2012)
AIMS: Vascular disease states are associated with endothelial dysfunction and increased production of reactive oxygen species derived from NADPH oxidases. However, it remains unclear whether a primary increase in superoxide production specifically in the endothelium alters the initiation or progression of atherosclerosis. METHODS AND RESULTS: Mice overexpressing Nox2 specifically in the endothelium (Nox2-Tg) were crossed with ApoE(-/-) mice to produce Nox2-Tg ApoE(-/-) mice and ApoE(-/-) littermates. Endothelial overexpression of Nox2 in ApoE(-/-) mice did not alter blood pressure, but significantly increased vascular superoxide production compared with ApoE(-/-) littermates, measured using both lucigenin chemiluminescence and 2-hydroxyethidium production (ApoE(-/-), 19.9 ± 6.3 vs. Nox2-Tg ApoE(-/-), 47.0 ± 7.0 nmol 2-hydroxyethidium/aorta, P< 0.05). Increased endothelial superoxide production increased endothelial levels of vascular cell adhesion protein 1 and enhanced macrophage recruitment in early lesions in the aortic roots of 9-week-old mice, indicating increased atherosclerotic plaque initiation. However, endothelial-specific Nox2 overexpression did not alter native or angiotensin II-driven atherosclerosis in either the aortic root or the descending aorta. CONCLUSION: Endothelial-targeted Nox2 overexpression in ApoE(-/-) mice is sufficient to increase vascular superoxide production and increase macrophage recruitment possible via activation of endothelial cells. However, this initial increase in macrophage recruitment did not alter the progression of atherosclerosis. These results indicate that Nox-mediated reactive oxygen species signalling has important cell-specific and distinct temporal roles in the initiation and progression of atherosclerosis.